2015
DOI: 10.1055/s-0035-1548824
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of Four Treatments in Patients with Graves’ Disease: a Network Meta-analysis

Abstract: Radioiodine+prednisone therapy might have the least probability of leading to an exacerbation or new appearance of ophthalmopathy, and radioiodine therapy might have the least probability of causing a recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“…In the meta-analysis conducted by Acharya et al, 37 radioiodine therapy significantly increased the incidence of developing or worsening of ophthalmopathy compared with antithyroid drugs (RR 5 4.23, 95% CI: 2.04, 8.77). Similarly, the other network meta-analysis by Ren et al 38 suggests that treatment with antithyroid drugs significantly decreased the incidence of new or deteriorative ophthalmopathy compared with radioiodine therapy (OR 5 2.958, 95% CI: 1.731, 4.735).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…In the meta-analysis conducted by Acharya et al, 37 radioiodine therapy significantly increased the incidence of developing or worsening of ophthalmopathy compared with antithyroid drugs (RR 5 4.23, 95% CI: 2.04, 8.77). Similarly, the other network meta-analysis by Ren et al 38 suggests that treatment with antithyroid drugs significantly decreased the incidence of new or deteriorative ophthalmopathy compared with radioiodine therapy (OR 5 2.958, 95% CI: 1.731, 4.735).…”
Section: Discussionmentioning
confidence: 82%
“…37,38 Our meta-analysis expands on these two earlier meta-analyses to provide a better evidence for an effective comparison between the two treatments. First, there are an enlarged number of included studies and sample sizes in our analysis, which gives greater power to detect the outcome differences between the two treatments.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Among 26 included MAs, 16 [14,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] were published in English, including two Cochrane reviews [35,37], the other 10 [40][41][42][43][44][45][46][47][48][49] were published in Chinese. The median year of the publications was 2010.…”
Section: Characteristics Of Included Masmentioning
confidence: 99%
“…Eleven MAs reported relapse rates following, different interventions, as described below. Two [32,36] concluded that there were statistically significant differences in recurrence rates between total and subtotal thyroidectomy (TT and ST, respectively) with TT superior to ST. One MA [28] concluded that RAI therapy significantly reduced the recurrence rate compared to surgery. However, another MA [14] drew a different conclusion, that is, that the rate of recurrence did not differ significantly between RAI and surgery.…”
Section: Relapses Of Hyperthyroidismmentioning
confidence: 99%